The Effect of Profitability and Leverage on Stock Return Rate Mediated by Dividend Policy (Empirical Study of Banks and Financial Institutions Listed on the Indonesia Stock Exchange) - Safitri, Niluh Santi (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study aims to examine the effect of profitability and leverage on stock returns with dividend policy as a mediating variable in banking sector companies and financial institutions listed on the Indonesia Stock Exchange (IDX). Profitability is measured using Return on Equity (ROE) and leverage is measured through Debt to Equity Ratio (DER). This study uses a quantitative approach with the path analysis method to identify direct and indirect relationships between variables. The data used is secondary data from the company's annual financial statements for the period 2016-2022. The results show that profitability has a significant positive influence on the rate of return on stocks, while leverage has no significant effect on the rate of return on stocks. Profitability also has a significant effect on dividend policy, indicating that the higher the profitability, the greater the dividend distributed. Conversely, leverage has a significant influence on dividend policy, which indicates that companies with high levels of leverage tend to distribute larger dividends. However, the dividend policy does not have a significant influence on the rate of return on shares. In addition, neither profitability nor leverage had a significant effect on the rate of return on shares through dividend policy mediation. This research makes a theoretical contribution by enriching the literature related to the influence of financial factors on stock performance. Practically, the results of this study are expected to provide insight to investors in making investment decisions by considering profitability and dividend policy as the main indicators.